From eruption to construction - Part A: Investigating the feasibility of volcanic material as partial replacement for cement in concrete - Arhusen, Mikaela; Lilja, Kajsa; Nyman, Filip; Osman, Ayel; Robinsson, Viktor; Toll Wester, Emil (Chalmers tekniska högskola / Institutionen för arkitektur och samhällsbyggnadsteknik (ACE), 2024)
Reducing the CO2 emissions during cement production is of utmost importance when it comes to combating the climate impact of the construction industry. Volcanic material (VM) has garnered a lot of attention due to its capability to function as a supplementary cementitious material (SCM) and its pozzolanic properties. Utilizing VM instead of cement in concrete has shown great potential when it comes to reducing environmental impact. This thesis examines the use of VM from Grindavik, Iceland, as an SCM. The methodology includes testing the reactivity of the VM through an MR3 test, measuring the compressive strength of the mortar, and examining the crystalline structure of different hydration phases using XRD. The mortar containing VM is compared to a reference sample containing only ordinary Portland cement (OPC), to determine the effects of the VM on the mortar. The results show that the VM has high reactivity in comparison to other natural pozzolans, and mortar containing the VM has high compressive strength. Replacing 40% of cement with VM in mortar gave the highest compressive strength, even surpassing pure OPC. To determine if the VM is suitable as an SCM further research needs to be done. Studying the hydration phases through a scanning electron microscopy (SEM), measuring tensile and flexural strength, as well as durability and workability, would provide further insight into the applicability of VM from Grindavik in concrete. In conclusion, the findings from this study show promising results when it comes to utilizing VM from Grindavik in concrete.